Factors associated with relationship formation, maintenance, and dissolution among lesbian couples in Iloilo City. - Bengan, Tricia Kay B. (2018.)
The study was conducted to explore the nature of relationship formation, maintenance, and dissolution among Filipino lesbian couples in Iloilo City. Twelve (12) lesbians served as respondents for the study. All the respondents must have been self-identified lesbians and have been in previous relationships with the same sex. The study is descriptive in nature, utilizing an interview guide as an instrument. Results in the study revealed that lesbians mostly meet in online sites, do not have courting process, have the same values, beliefs, and personality with their partners, and communicate through personal meeting. Majority pointed out cheating or presence of a third party as the reason for their break-up.
Research Project (Undergraduate, Bachelor of Arts (Psychology) College of Arts and Sciences, University of the Philippines, Miagao, Iloilo. 2018.
Keywords: Lesbian Couples -- Iloilo City